Al Capone does my shirts - Choldenko, Gennifer, 1957- (New York : Putnam's, 2004)
A twelve-year-old boy named Moose moves to Alcatraz Island in 1935 when guards' families were housed there, and has to contend with his extraordinary new environment in addition to life with his autistic sister.
Includes bibliographical references.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
4.0
5-8
Keywords: United States Penitentiary, Alcatraz Island, California -- Juvenile fiction; United States Penitentiary, Alcatraz Island, California -- Fiction; United States Penitentiary, Alcatraz Island, California -- Fiction; Autism -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Families -- Juvenile fiction; Historical fiction; Autism -- Fiction; Brothers and sisters -- Fiction; Family problems -- Fiction; Historical fiction; Autism -- Fiction; Family life -- Fiction; Historical fiction; Siblings -- Fiction; Alcatraz Island (Calif.) -- History -- Juvenile fiction; Alcatraz Island (Calif.) -- History -- Fiction; Alcatraz Island (Calif.) -- History -- Fiction